ΔNp63 activates EGFR signaling to induce loss of adhesion in triple-negative basal-like breast cancer cells - Holcakova, Jitka; Nekulova, Marta; Orzol, Paulina; Nenutil, Rudolf; Podhorec, Jan; Svoboda, Marek; Dvorakova, Petra; Pjechova, Mariana; Hernychova, Lenka; Vojtesek, Borivoj; Coates, Philip J (Breast cancer research and treatment, 2017)
PURPOSE: The basal-A subtype of triple-negative breast cancer is characterized by high levels of ΔNp63. Various functions have been proposed for p63 in breast cancer initiation and growth, and p63 mediates chemotherapeutic response in a subset of triple-negative breast cancers. We investigated the signaling pathways that are controlled by ΔNp63 in basal-A triple-negative breast cancer. METHODS: Human basal-A triple-negative breast cancer cell lines with ΔNp63α induction or inhibition were studied, along with primary human triple-negative breast cancer tissues. Proteomic, phospho-kinase array, mRNA measurements, and immunohistochemistry were employed. RESULTS: Global phosphoproteomics identified increased EGFR phosphorylation in MDA-MB-468 cells expressing ΔNp63α. ΔNp63α expression increased EGFR mRNA, total EGFR protein, and phospho-EGFR(Y1086), whereas silencing endogenous ΔNp63 in HCC1806 cells reduced both total and phospho-EGFR levels and inhibited the ability of EGF to activate EGFR. EGFR pathway gene expression analysis indicated that ΔNp63 alters EGFR-regulated genes involved in cell adhesion, migration, and angiogenesis. Addition of EGF or neutralizing EGFR antibodies demonstrated that EGFR activation is responsible for ΔNp63-mediated loss of cellular adhesion. Finally, immunohistochemical staining showed that p63-positive triple-negative breast cancers were more likely to express high levels of EGFR than p63-negative cancers, corroborated by in silico analysis of gene expression profiling data. CONCLUSIONS: These data identify EGFR as a major target for ΔNp63 regulation that influences cancer cell adhesion in basal-like triple-negative breast cancer.
Keywords: regulace genové exprese u nádorů; metastázy nádorů; proliferace buněk; Female; ErbB Receptors; erbB receptory; Cell Line, Tumor; invazivní růst nádoru; ženské pohlaví; EGFR; Gene Expression Regulation, Neoplastic; p63; buněčná adheze; lidé; triple-negativní karcinom prsu; proteomika; Cell Adhesion; signální transdukce; membránové proteiny; Triple Negative Breast Neoplasms; Signal Transduction; epidermální růstový faktor; Proteomics; Metastasis; Cell Proliferation; Membrane Proteins; Invasion; Breast cancer; Neoplasm Invasiveness; Neoplasm Metastasis; Adhesion; Epidermal Growth Factor; nádorové buněčné linie; Humans